Antiviral Lectins from Red and Blue-Green Algae Show Potent In Vitro and In Vivo Activity against Hepatitis C Virus - Takebe, Yutaka; Saucedo, Carrie J.; Lund, Garry; Uenishi, Rie; Hase, Saiki; Tsuchiura, Takayo; Kneteman, Norman; Ramessar, Koreen; Tyrrell, D. Lorne J.; Shirakura, Masayuki; Wakita, Takaji; McMahon, James B.; et al. (PLOS ONE, 2013)
Hepatitis C virus (HCV) infection is a significant public health problem with over 170,000,000 chronic carriers and infection rates increasing worldwide. Chronic HCV infection is one of the leading causes of hepatocellular carcinoma which was estimated to result in ∼10,000 deaths in the United States in the year 2011. Current treatment options for HCV infection are limited to PEG-ylated interferon alpha (IFN-α), the nucleoside ribavirin and the recently approved HCV protease inhibitors telaprevir and boceprevir. Although showing significantly improved efficacy over the previous therapies, treatment with protease inhibitors has been shown to result in the rapid emergence of drug-resistant virus. Here we report the activity of two proteins, originally isolated from natural product extracts, which demonstrate low or sub-nanomolar in vitro activity against both genotype I and genotype II HCV. These proteins inhibit viral infectivity, binding to the HCV envelope glycoproteins E1 and E2 and block viral entry into human hepatocytes. In addition, we demonstrate that the most potent of these agents, the protein griffithsin, is readily bioavailable after subcutaneous injection and shows significant in vivo efficacy in reducing HCV viral titers in a mouse model system with engrafted human hepatocytes. These results indicate that HCV viral entry inhibitors can be an effective component of anti-HCV therapy and that these proteins should be studied further for their therapeutic potential.